Efectos de actividades de psicomotricidad en las habilidades sociales en los niños de cinco años de la institución educativa inicial N°333 Cushillo Cocha 2024 - Coello Guerrero, Melchi (2025)
The purpose of this research study is to determine the effects of the application of psychomotor activities on the development of social skills in five year-old children of the Institución Educativa Inicial N°333 Cushillo Cocha 2024. This study, with a quantitative approach, It is classified as applied type research. The design adopted has been quasi-experimental, in two groups. The population under study was made up of all five-year-old boys and girls, totaling 38 children. For data collection, the observation technique has been used, using an observation guide as an instrument. Regarding the validity of the instrument, it has been evaluated by a team of experts with extensive experience in the area. The results obtained, the statistical value obtained was tc = 6.322, with a p-value of 0.000, which is less than the significance level α = 0.05. This result indicates that there is a significant difference between the two groups, with the experimental group showing a more pronounced improvement compared to the control group. It is concluded, the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. This implies that the application of psychomotor activities has positive effects on the development of children's social skills.